Structural affairs - Gethmann, Daniel; Enzenhofer, Lisa Maria (Graz Architektur Magazin ;, 2016)
Increasingly, innovative construction design relies on interdisciplinary cooperation between architects, engineers and the construction industry. GAM.12 - Structural Affairs takes a look at the mechanics of cooperation in the dynamic work processes of contemporary architecture. New digital methods, materials and production methods require the participation of more and more specialised stakeholders in the design and construction process - they influence and determine the respective architectural design process from the outline idea through to detailed design and construction. GAM.12 investigates the potential and synergies of this development for the architectural process, and presents current projects and theoretical positions for discussion.